Raised serum levels of IGFBP-1 and IGFBP-2 in idiopathic pulmonary fibrosis. Issue 1 (December 2016) - Guiot, J.; Bondue, B.; Henket, M.; Corhay, J.; Louis, R.
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a chronic lung disorder of unknown origin, which ultimately leads to death. Several growth factors such as IGFs (insulin-like-growth factor) and IGFBPs (insulin like growth factor binding proteins) seem to take part to the pathogenesis. We evaluated IGFs and IGFBPs in serum from patients with IPF and healthy subjects including 24 untreated IPF and 26 IPF receiving anti-fibrotic therapy and to compare them with healthy subjects. Methods Serum of 50 idiopathic pulmonary fibrosis and 55 healthy subjects (HS) were analysed by ELISA for IGFs and IGFBPs, TGF-β and KL-6, the latter being tested as positive control in IPF. Results Serum levels of IGFBP-1 and IGFBP-2 and KL-6 were significantly higher in the IPF group than in the healthy subjects (p < 0.05, p < 0.001 andp < 0.0001 respectively) while the picture was inversed regarding IGFs. By contrast there was no significant difference between the groups with respect to TGF-β. IGFBP-2 was significantly reduced in the patients with specific anti-fibrotic therapy pirfenidone and nintedanib compared to untreated patients (p < 0.05) but still significantly elevated in comparison to HS (p < 0.001). Conclusion Serum IGFBP-1 and −2 are increased in idiopathic pulmonary fibrosis and IGFBP-2 may be reduced by anti-fibrosing therapy. IGFBPs may be promising biomarkers in IPF.